Behaviour of castellated beam-to-column end-plate connection under monotonic load. (December 2021) - Jia, Lianguang; Li, Qiurong; Bi, Ran; Dong, Yang
Abstract: The development of plastic hinges in a steel frame structure with steel beam-to-column end-plate connection joints by strengthening the end-plate area is a widely used design concept. This study explores the realization of this design concept with a beam web opening and without end-plate stiffening. The factors that impact the mechanical properties and failure modes of these joints are the end-plate thickness, opening diameter, opening position, and opening type. These parameters are tested for monotonic loading of six beam-column joints, and 220 finite element models are parametrically analysed. Additionally, the development of plastic hinge of the beam based on the development trend of maximum strain of each component section is studied. The initial rotational stiffness, ductility, bearing capacity, deformation capacity, and failure mode are used as the evaluation criteria to assess the behaviour of this joint. The research indicates that a castellated steel beam-to-column end-plate connection can realize the occurrence of plastic hinge and exhibit good ductility and load-bearing performance. This study highlights the premise that the beam web opening and end-plate thickness parameters must be within a specific range to achieve accurate results; additionally, the division method of the interval of parameters is described. The influence of end-plate thickness on the working mechanism of the connection is clarified, and the mechanical properties and failure modes of connections under different parameter intervals are studied. This study proposes a method for calculating the initial rotational stiffness of the connection to achieve good accuracy by considering the participation of the components on the beam in the rotation of the connection.